Hedging against foreign exchange risk of peso-dollar rates using futures contracts with different maturities - Roxas, Arniel E. (UP Los Baños Journal, 2015)
Currency trading is the act of buying or selling a currency in exchange or another currency. It involves risk due to the fluctuations of the exchange rates. The said risk can be minimized through hedging using financial instruments such as futures. A futures is an agreement to but or sell an underlying asset by a certain date in the future for a certain price.